Java 7 for absolute beginners - Bryant, Jay (Expert's voice in Java., 2012)
Java 7 Programming for Absolute Beginners introduces you to the new core, open source Java Development Kit. Its focus is on practical knowledge and its completeness - it provides all the bits and pieces an utter novice needs to get started with programming in Java.